A direct-conversion receiver for the 3G WCDMA standard. - Gharpurey, R. (IEEE Journal of solid state circuits)
A highly integrated direct-conversion receiver that satisfies requirements of the third-generation wide-band code-division multiple-access mobile phone standard is described. The receiver integrated circuit includes the front-end low-noise amplifier, downconversion mixers, baseband variable-gain amplifiers, channel-select filters, and the frequency synthesizer. External components are limited to matching elements required for the low-noise amplifier and the mixers and two passive band-select filters. The receiver is implemented in a SiGe BiCMOS process and consumes a total current of 46 mA from a 2.7-V supply.